Contribution to the study of the blood supply of the sinus node in asinines (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1972)
The arterial blood supply of the sinus node has been studied in 15 asinines (24 females and 21 males). The sinus node was nourished by the ramus proximalis atrii sinistri in 40 (88.9% ± 4.6) of the examined hearts; by the ramus proximalis atrii dextri in 5 (11.1% ± 4.6) of the examined pieces. Arterial anastomoses were observed in 5 cases between collaterals from rami proximalis atrii sinistri and distalis atrii dextri; in 4 cases between collaterals from rami proximalis atrii sinistri and proximalis atrii dextri. There was no sexual influence in the pattern of the blood supply to the sinus node.